I don't really know what you're trying to ask because
x = -2 and x=6 are your roots.
But if you want to convert them back to their equation form,
get the other side of the equation to be 0.
x = 6
x - 6 = 0
x = -2
x + 2 = 0
so your original equation had something like (x+2)(x-6)
Answer:
(x,y,z) -> (2,4,1)
Step-by-step explanation:
-7x + y + z = -9
-7x + 5y - 9z = -3
7x - 6y + 4z = -6
Pick two pairs:
-7x + 5y - 9z = -3
7x - 6y + 4z = -6
and
-7x + y + z = -9
-7x + 5y - 9z = -3
Eliminate the same variable from each system:
-7x + 5y - 9z = -3
7x - 6y + 4z = -6
+ 5y - 9z = -3
- 6y + 4z = -6
<u><em>-1y - 5z = - 9</em></u>
-7x + y + z = -9
-7x + 5y - 9z = -3
-7x + y + z = -9
7x - 5y + 9z = 3
<u><em>-4y - 10z = -6</em></u>
Solve the system of the two new equations:
-1y - 5z = - 9 -> -4 ( -1y - 5z = - 9) -> 4y + 20z = 36
-4y - 10z = -6 -> -4y - 10z = -6 -> -4y - 10z = -6
10z = 30
Thus, z = 3
-4y - 10z = -6
-4y - 10(3) = -6
-4y - 30 = -6
-4y = 24
Thus, y = -6
Substitute into one of the original equations:
-7x + y + z = -9
-7x + (-6) + (3) = -9
7x + -3 = -9
7x = -6
x =
Answer:
Its when you add angles together
Its when two angles are congruent
Step-by-step explanation:
If you do 81 x 9 which equals 729. If you want to check, you do 729 divided by 9 and you get 81.